Power dynamics in the student-teacher relationship in clinical settings. (February 2017) - Chan, Zenobia CY; Tong, Chien Wai; Henderson, Saras
Abstract: Background: Among many factors that influence clinical learning, the teacher-student relationship has been found to be crucial. The imbalance of power in that relationship tends to be regarded as negative, but how students actually perceive the power within the relationship is unknown. Aim: This study explored nurse students' perceptions of the power dynamics in the teacher-student relationship during their clinical placement. Design: A descriptive qualitative study. Methods: A total of 51 students were recruited from a nursing school in Hong Kong. Seven focus group interviews consisted of three groups of Year 3 students (n = 26) and four groups of final year students (n = 25). A semi-structured interview guideline was designed. Content analysis was employed to analyse the research data. Results: The three core themes that emerged from the qualitative data were: (1) meanings of power – avoiding doing harm to patients; (2) the desired power dynamics – master vs apprentice; and (3) enhancing the clinical learning experience. Conclusions: The dominant theme in the participants' discourse was that teachers should possess more power than students in order to prevent students from causing harm to patients. The consensus was that the teacher's power in supervising students' clinical practice is accepted and necessary for the benefit of patient safety. The cultural relevance of the power dynamics in the teacher-student relationship should be embraced in order to understand the student's perspective. Highlights: Revealed that teachers should possess more power than students in order to prevent students from causing harm to patients Considered cultural relevance of the power dynamics in the teacher-student relatonship